A Mapping Study of Veterinary Literature on Perceptions and Attitudes of Female Canine Spaying - Fausak, Erik Davis (Frontiers in Veterinary Science, 2020)
This is a mapping study conducted to evaluate characteristics of where content that engages in perspectives or attitudes on female dog spaying is published. Three databases: CAB Direct, PubMed and Scopus were systematically searched. 84 out of 642 papers were identified and screened for relevance on attitudes or perceptions of female canine spaying. These 84 articles were then examined for recurring authors, institutional representation, and publisher information. Additionally, information regarding the population being addressed, veterinarian or client, was noted with most literature addressing the veterinary perspective. Many important articles were published in a wide array of journals from many countries which suggests the importance of not just browsing journals but searching for relevant literature in databases like CAB Abstracts and Medline.